Untersuchungen zur Wirtschaftlichkeit von Building Information Modeling (BIM) in der Planungs- und Realisierungsphase von Bauprojekten - Deubel, Maximilian (Karlsruher Reihe Technologie und Management im Baubetrieb, 2021)
BIM is seen as an opportunity to complete construction projects more reliably. At the same time, various challenges are discussed that make the introduction more difficult. So far, there has been less focus on investigating the economic efficiency of BIM itself. The aim is therefore to make the expenses and benefits of BIM determinable. As a result, BIM users will receive assistance in determining the economic efficiency of individual BIM use cases and thus of BIM as a whole.